Fatal outcome of human influenza A (H5N1) is associated with high viral load and hypercytokinemia - Simmons, Cameron (2018)
Avian influenza A (H5N1) viruses cause severe disease in humans, but the basis for their virulence remains unclear. In vitro and animal studies indicate that high and disseminated viral replication is important for disease pathogenesis. Laboratory experiments suggest that virus-induced cytokine dysregulation may contribute to disease severity. To assess the relevance of these findings for human disease, we performed virological and immunological studies in 18 individuals with H5N1 and 8 individuals infected with human influenza virus subtypes. Influenza H5N1 infection in humans is characterized by high pharyngeal virus loads and frequent detection of viral RNA in rectum and blood. Viral RNA in blood was present only in fatal H5N1 cases and was associated with higher pharyngeal viral loads. We observed low peripheral blood T-lymphocyte counts and high chemokine and cytokine levels in H5N1-infected individuals, particularly in those who died, and these correlated with pharyngeal viral loads. Genetic characterization of H5N1 viruses revealed mutations in the viral polymerase complex associated with mammalian adaptation and virulence. Our observations indicate that high viral load, and the resulting intense inflammatory responses, are central to influenza H5N1 pathogenesis. The focus of clinical management should be on preventing this intense cytokine response, by early diagnosis and effective antiviral treatment.